Comparison of morbidity associated with non-descent vaginal hysterectomy and total abdominal hysterectomy - Ghadei, Ranjita; Mishra, Gupteswar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: In the present scenario of importance non-invasive surgery, there is increase in interest and requirement of vaginal hysterectomy for non-prolapsed uterus, i.e. non-descent vaginal hysterectomy (NDVH) due to its scarless surgery. it has much more advantages than that of abdominal hysterectomy in term of cosmesis, lesser duration of surgery, lesser intraoperative complication, lesser post-operative morbidity and early resumption to work. The aim of the present study is to asses and compare various factors like duration of surgery, intraoperative blood loss, intraoperative and postoperative complication postoperative morbidities, pain perception on 3rd post-operative day, post-operative ambulation, duration of hospital stay, time taken to resume normal work, follow up complains and afterall to decide the appropriate route of hysterectomy for benign conditions. Methods: Hundreds of patients were selected as per the criteria. They were divided into two groups NDVH (non-descent vaginal hysterectomy) and TAH (total abdominal hysterectomy) according to the inclusion criteria. Above mentioned factors are compared between the two groups. Results: Duration of surgery, intraoperative blood loss, intraoperative complications, post-operative morbidities and complications, duration of hospital stay, time required to resume normal work are less in NDVH group. Conclusions: Non-descent vaginal hysterectomy is a better alternative to abdominal hysterectomy for benign conditions.